SMN protein is required throughout life to prevent spinal muscular atrophy disease progression. Issue 1 (9th August 2021) - Zhao, Xin; Feng, Zhihua; Risher, Nicole; Mollin, Anna; Sheedy, Josephine; Ling, Karen K Y; Narasimhan, Jana; Dakka, Amal; Baird, John D; Ratni, Hasane; Lutz, Catherine; Chen, Karen S; et al.
Abstract: Spinal muscular atrophy (SMA) is caused by the loss of the survival motor neuron 1 ( SMN1 ) gene function. The related SMN2 gene partially compensates but produces insufficient levels of SMN protein due to alternative splicing of exon 7. Evrysdi™ (risdiplam), recently approved for the treatment of SMA, and related compounds promote exon 7 inclusion to generate full-length SMN2 mRNA and increase SMN protein levels. SMNΔ7 type I SMA mice survive without treatment for ~17 days. SMN2 mRNA splicing modulators increase survival of SMN∆7 mice with treatment initiated at postnatal day 3 (PND3). To define SMN requirements for adult mice, SMNΔ7 mice were dosed with an SMN2 mRNA splicing modifier from PND3 to PND40, then dosing was stopped. Mice not treated after PND40 showed progressive weight loss, necrosis, and muscle atrophy after ~20 days. Male mice presented a more severe phenotype than female mice. Mice dosed continuously did not show disease symptoms. The estimated half-life of SMN protein is 2 days indicating that the SMA phenotype reappeared after SMN protein levels returned to baseline. Although SMN protein levels decreased with age in mice and SMN protein levels were higher in brain than in muscle, our studies suggest that SMN protein is required throughout the life of the mouse and is especially essential in adult peripheral tissues including muscle. These studies indicate that drugs such as risdiplam will be optimally therapeutic when given as early as possible after diagnosis and potentially will be required for the life of an SMA patient.